The Effect of Climate Change to the Farm Shrimp Growth and Production: An Empirical Analysis - Aziz, Nazrina; Misiran, Masnita; Sear Yin, Tan; Hooi Yee, Tan; Jia Hui, Ng; Yun Pei, Lu; Idayu Mahat, Nor; Mat Yusof, Muhammad; Shah Ruddin, Amir (International Journal of Engineering and Technology, 2018)
The shrimp growth and production can be measured through several components such as the harvest ton, mean body weight, survival rate and feed conversion ratio. According to previous studies, the shrimp feed conversion ratio should have a positive relationship with their mean body weight. Nevertheless, in real scenario, high feed conversion ratio does not necessarily implies maximum increment of mean body weight. The measurement of those components usually can be influenced by many factors such as climates, stocking density and day of culture. This study in particular explores the effect of climates on productivity of the shrimp species, Penaeus Vannamei and investigates whether feed conversion ratio influences the mean body weight when stocking are done at different climate season. First, the one-way MANOVA was used to measure the effect between the climate seasons and P. Vannamei production.  Then, the regression analysis was apply to measure the relationship between P. Vannamei feed conversion ratio and mean body weight for different climate seasons. Finally, to find the best season for sustainable production of P. Vannamei, the average score of P. Vannamei production was measured according to their stocking climate season. Result revealed that dry season was more favorable for the growth and production of P. Vannamei compared to wet season.